An analysis of mergers in the presence of renewable energy integration uncertainty. - Daher, Wassim; Elnaboulsi, Jihad; Fikru, Mahelet G.; Gautier, Luis (My University, 2024)
We study the incentives to merge for energy producers in the presence of distributed renewable energy producers. Utilizing a Cournot model, we explore how uncertainty surrounding the cost of grid integration influences the profitability of mergers, where uncertainty comes in the form of an industry-wide (or common) and private shocks. We find that the effect of these uncertainties on merger profitability depends on average energy grid integration costs, the size of the merger, and quality of private information. Overall, results suggest that mergers are more likely to be profitable when firms can effectively absorb private shocks due to the scale of the merger, unless average grid integration costs become too high. The incentives to merge are less clear-cut in the presence of an industry-wide (common) shock, unless the quality of private information is high enough.
Keywords: Empresas - Fusión; Reorganización de empresas; Mergers and acquisitions; Energy integration costs; Uncertainty